Health Educator Participation in Virtual Micro-Credentialing Increases Physical Activity in Public Health Competencies - Dysart, Anna; Balis, Laura E.; Daniels, Bryce T.; Harden, Samantha M. (Frontiers in Public Health, 2021)
Background: Physical activity is an important component of leading a healthy life. Public health is one of the nine major sectors for disseminating information about physical activity and increasing the physical activity of the general public. Purpose: Increase competency among Cooperative Extension agents (i.e., public health workers) on selecting, delivering, and evaluating physical activity programs through a theory-based online training program. Methods: Cooperative Extension agents from two states were invited to participate via statewide listservs. Participants were invited to attend sessions, complete competency checks, and between-session assignments each week. The study was conducted using a video conferencing platform. The intervention was 9 weeks from June to July 2020 and had 130 participants. Pre- and post-program surveys included physical activity competencies and validated scales for flourishing and physical activity status. Data for competencies pre and post were analyzed using the Wilcoxon signed rank test, p < 0.01. Physical activity and flourishing pre and post were compared using t-tests, p < 0.05. Results: Physical activity in public health competency increased significantly (p < 0.00) as did agents' personal physical activity levels (p < 0.05). Changes in flourishing were not significant (p < 0.09) but trended in the hypothesized direction. Conclusions: The online competency-based training program significantly improved Cooperative Extension agents' knowledge of physical activity guidelines and physical activity program implementation. Future work is needed related to the scalability of the training program.